Sculpting nuclear envelope identity from the endoplasmic reticulum during the cell cycle - Pallavi Deolal; Julia Scholz; Kaike Ren; Helena Bragulat-Teixidor; Shotaro Otsuka (Nucleus)
The nuclear envelope (NE) regulates nuclear functions, including transcription, nucleocytoplasmic transport, and protein quality control. While the outer membrane of the NE is directly continuous with the endoplasmic reticulum (ER), the NE has an overall distinct protein composition from the ER, which is crucial for its functions. During open mitosis in higher eukaryotes, the NE disassembles during mitotic entry and then reforms as a functional territory at the end of mitosis to reestablish nucleocytoplasmic compartmentalization. In this review, we examine the known mechanisms by which the functional NE reconstitutes from the mitotic ER in the continuous ER–NE endomembrane system during open mitosis. Furthermore, based on recent findings indicating that the NE possesses unique lipid metabolism and quality control mechanisms distinct from those of the ER, we explore the maintenance of NE identity and homeostasis during interphase. We also highlight the potential significance of membrane junctions between the ER and NE.